PERTUMBUHAN Mucuna bracteata PADA BERBAGAI KOMPOSISI MEDIA TANAM DAN VOLUME PENYIRAMAN - Titin Setyorini; Mangihut Tua Raja; Yohana Theresia Maria Astuti (Program Studi Agroteknologi INSTIPER, 2017)
Mucuna bracteata is a cover crop that is commonly used in oil palm plantations. It has many advantages, such as rapidly growing, preventing erosion on open land and suppressing weed growth. The research aims to determine the effect of various compositions planting medium with addition of organic and inorganic fertilizers and watering volume on the growth of Mucuna bracteata. The research was conducted in Kebun Pendidikan dan Penelitian (KP2) Institut Pertanian STIPER Yogyakarta, from April to July 2016. Completely Randomized Design (CRD) factorial consisting of two factors was applied as experimental design. The first factor was growing media consisting of four levels, namely P0 (regosol, without fertilizer), P1 (regosol + NPK), P2 (regosol + manure), P3 (regosol + compost). The second factor was watering volume consisting of three levels, namely V1 (200 ml/day), V2 (400 ml/day), and V3 (600 ml/day). Analysis of variance (ANOVA) and Duncan's Multiple Range Test (DMRT), both with significance level of 5%, were then used to find out whether significant differences among treatments, were existed. Regression was used if ANOVA showed no significant differences among treatment. The result showed that there was no interaction between treatment, growing media and watering volume on Mucuna bracteata’s growth. Regosol and manure was the best media to support plant growth Mucuna bracteata, while the watering volume was not. Keywords : Growth, Mucuna bracteata, growing medium, watering volume